2011
DOI: 10.1073/pnas.1101892108
|View full text |Cite
|
Sign up to set email alerts
|

An antigenic peptide produced by reverse splicing and double asparagine deamidation

Abstract: A variety of unconventional translational and posttranslational mechanisms contribute to the production of antigenic peptides, thereby increasing the diversity of the peptide repertoire presented by MHC class I molecules. Here, we describe a class I-restricted peptide that combines several posttranslational modifications. It is derived from tyrosinase and recognized by tumor-infiltrating lymphocytes isolated from a melanoma patient. This unusual antigenic peptide is made of two noncontiguous tyrosinase fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
122
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 55 publications
1
122
2
Order By: Relevance
“…This reversed cleavage has also been shown for other proteases including the proteasome that then would yield new spliced Ags that are not genetically coded yet can be presented to the immune system (5)(6)(7)(8)(9). To date, five spliced Ags that are immunogenic in vivo have been described: [RTK][QLYPEW] (5), [NTYAS][PRFK] (6), [SLPRGT] [STPK] (7), [IYMDGT][ADFSF] (8), and [RSYVPLAH][R] (9), all of which are produced by the proteasome through a transpeptidation mechanism (5,7,10,11). During normal proteasomal peptide hydrolysis, the N-terminal threonine residue of a catalytically active subunit reacts with the scissile peptide bond to form an O-acyl enzyme intermediate, resulting in the release of the C-terminal part of the peptide.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This reversed cleavage has also been shown for other proteases including the proteasome that then would yield new spliced Ags that are not genetically coded yet can be presented to the immune system (5)(6)(7)(8)(9). To date, five spliced Ags that are immunogenic in vivo have been described: [RTK][QLYPEW] (5), [NTYAS][PRFK] (6), [SLPRGT] [STPK] (7), [IYMDGT][ADFSF] (8), and [RSYVPLAH][R] (9), all of which are produced by the proteasome through a transpeptidation mechanism (5,7,10,11). During normal proteasomal peptide hydrolysis, the N-terminal threonine residue of a catalytically active subunit reacts with the scissile peptide bond to form an O-acyl enzyme intermediate, resulting in the release of the C-terminal part of the peptide.…”
mentioning
confidence: 99%
“…Because spliced Ags may mediate T cell responses to cancer, transplants, and viral infection, predicting their generation would be important for the development of vaccines and immunotherapies or to pharmacologically suppress T cell responses (12). Although proteasomal peptide ligation can readily be detected in vitro (11,15), identifying spliced Ags in vivo has proven to be difficult with only five immunomodulatory spliced epitopes identified (5)(6)(7)(8)(9). Classically, novel epitopes are identified by cell surface elution and mass spectroscopy (MS) analysis, followed by matching against protein databases (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PCPS would only depends on the proteasomal site-specific cleavage strength (SCS), which determines how frequently proteasomes cleaves specific peptide bond (5,6). Interestingly, Dalet et al identified a single PSP to be generated in absence of proteolysis, albeit with an extremely low efficiency, in a reaction that they defined as "condensation" (8) and that will be reported here as hydrolysis ϩ transpeptidation to discriminate it from the direct transpeptidation reaction.…”
mentioning
confidence: 99%
“…A second peptide, encoded by the melanoma differentiation Ag gp100 PMEL17 is made by the association of fragments RTK and QLYPEW, which are distant of 4 aa in the parent protein (25). The two other spliced peptides described were produced by re-*Ludwig Institute for Cancer Research, B-1200 Brussels, Belgium; † Waloon Excellence in Life Sciences and Biotechnology, B-1200 Brussels, Belgium; ‡ de Duve Institute, Université Catholique de Louvain, B-1200 Brussels, Belgium; verse splicing, that is, splicing of peptide fragments in the reverse order to that in which they appear in the parental protein (26,27). One of them is a minor histocompatibility Ag created by a polymorphism in the SP110 nuclear phosphoprotein gene and made after splicing of peptide segments STPK and SLPRGT to create the antigenic peptide SLPRGTSTPK (27).…”
mentioning
confidence: 99%